Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/asj/sjw264
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Animation Deformity on Quality of Life in Post-Mastectomy Reconstruction Patients

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 6 publications
1
69
3
Order By: Relevance
“…This difference would be anticipated due to the absence of the breast parenchyma to camouflage the deformity, as well as the probability of more aggressive muscle separation inferomedially to accommodate generally larger breast reconstruction implants. Compared with the recent study by Becker and Fregosi 2 , our patients were slightly less aware of AD (75.6% versus 80%). Whereas Becker and Fregosi 2 found that 36% of patients experienced severe AD, 11% of ours experienced severe AD.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…This difference would be anticipated due to the absence of the breast parenchyma to camouflage the deformity, as well as the probability of more aggressive muscle separation inferomedially to accommodate generally larger breast reconstruction implants. Compared with the recent study by Becker and Fregosi 2 , our patients were slightly less aware of AD (75.6% versus 80%). Whereas Becker and Fregosi 2 found that 36% of patients experienced severe AD, 11% of ours experienced severe AD.…”
Section: Discussioncontrasting
confidence: 98%
“…This may not only be unsightly and embarrassing for the breast reconstruction patient but may also cause discomfort with certain activities; in more extreme cases, AD can be emotionally and physically debilitating. 2 Although Spear et al 1 found that 53% of patients note AD after submuscular breast augmentation, we found this number to be notably higher in the breast reconstruction population (75.6%). This difference would be anticipated due to the absence of the breast parenchyma to camouflage the deformity, as well as the probability of more aggressive muscle separation inferomedially to accommodate generally larger breast reconstruction implants.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Breast animation deformity (BAD), also referred to as breast distortion or 'jumping breast', is characterised by an unsightly deformation of the whole breast, breast skin or nipple-areolar complex [10]. The consequences of BAD have been described in cosmetic surgery following subpectoral breast augmentation by Spears in 2009 [11] although have not been widely addressed until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the aesthetic population, the reconstructive patient population is more sensitive to the negative impacts of animation deformity. In a study by Becker and Fregosi of 25 patients after mastectomy with implants placed in a subpectoral plane, almost all patients had animation deformity and 80% of the patients were bothered by the animation deformity and 45% were bothered by it to a significant degree [2].…”
mentioning
confidence: 99%